Analysis of Comorbidities of Alcohol Use Disorder - Ebrahimi, Ali; Wiil, Uffe Kock; Mansourvar, Marjan; Naemi, Amin; Andersen, Kjeld; Nielsen, Anette Sogaard (2021 IEEE Symposium on Computers and Communications (ISCC), 2021)
Alcohol Use Disorder (AUD) is a clinical diagnosis based on signs and symptoms that are related to excessive alcohol use and it increases the risk of many clinical conditions, psychological instabilities, and social issues. In this study, we aim to identify the comorbidities of Hazardous and Harmful drinkers. We obtained comorbidity networks for Hazardous, and Harmful drinkers using social network analysis techniques. Each network consists of several nodes that represent the diagnostic codes that patients were given during their hospitalization. To precisely identify the most exclusive comorbidities in each drinking group, we proposed a four-step process based on a machine learning algorithm and aggregation functions. Our findings show that the majority of the identified comorbidities in the Harmful drinking group are related to ICD-10 chapters XI, XIX, and XIII. The comorbidities of the Hazardous drinking group, however, did not present a similarly clear pattern.